My Journey: DFD (Data Flow Diagram) for Digital Planners and Travel Guide Applications in Indonesia - Setiyawan, M. Irsyad; Ardiansyah, Mohammad Fakhrul; Ocktavia, Giovanny Dwi Ayu; H., Raja Muhammad Akmal A.; Siswandini, Nabila Putri (Gemilang Maju Publikasi Ilmiah (GMPI), 2023)
Tourism is one of the important aspects in terms of increasing income in an area as well as people's welfare. The presence of a well-managed tourism area will improve the welfare of the community. Indonesia has a region that is very rich in tourism, but it is unfortunate that in Indonesia there are still obstacles in the information system so that tourists have difficulty in finding tourist attractions and facilities located in the area. Although Indonesia already has a relatively comprehensive online search, Indonesia does not fully help with access, accommodation cost planning for traveling. This made us have the idea to create a My Journey application for travel planning and guidance . This application is very appropriate to be applied in this moment of the modern era because technological advancements require us to do everything through digital. Development of digital applications My Journey By using GPS and DFD (Data Flow Diagram) Design Method to facilitate the service of the application.The My Journey application is equipped with location routes and accommodation advice to get to tourist attractions, especially accommodation access using public transportation so that tourists can easily go to tourist attractions with the help of the My Journey application. In this, My Journey application will help the tourists in manage and arrange travel tour planning following the needs that are needed. In addition, this application also provides an online souvenir sales service for MSME development and ticket purchase as well as providing rental services for vehicles, equipment, and other things that support online in one application . With this application, it is expected that both local and international tourists will find it easy to get information about the tours visited, as well as a form of tourism promotion in Indonesia.